2021
DOI: 10.1155/2021/6014202
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Ferroptosis‐Related Gene Signature for Predicting Prognosis and the Immune Microenvironment in Gastric Cancer

Abstract: Ferroptosis is a mode of regulated cell death that depends on iron and plays pivotal roles in regulating various biological processes in human cancers. However, the role of ferroptosis in gastric cancer (GC) remains unclear. In our study, a total of 2721 differentially expressed genes (DEGs) were filtered based on The Cancer Genome Atlas (TCGA) ( n = 375 ) dataset. Weighted gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“… 60 SLC1A5 reflected the status of the tumor immune microenvironment in gastric cancer. 61 These findings revealed that SLC1A family genes had an impact on immune infiltration, and varying levels of genetic alteration in LUAD. This study was a pioneer work to a comprehensive analysis of the expression and major role of SLC1A family genes in LUAD based on bioinformatics analysis, but the main limitations of our research should be noted.…”
Section: Discussionmentioning
confidence: 90%
“… 60 SLC1A5 reflected the status of the tumor immune microenvironment in gastric cancer. 61 These findings revealed that SLC1A family genes had an impact on immune infiltration, and varying levels of genetic alteration in LUAD. This study was a pioneer work to a comprehensive analysis of the expression and major role of SLC1A family genes in LUAD based on bioinformatics analysis, but the main limitations of our research should be noted.…”
Section: Discussionmentioning
confidence: 90%
“…lncRNA LINC00336 inhibits ferroptosis in lung cancer by functioning as a competing endogenous RNA [35]. In addition, some studies constructed the FRGs signature to predict prognosis of several cancers, such gliomas, gastric cancer and lung adenocarcinoma [36][37][38]. However, prognostic models based on FRLs in THCA are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis-related genes NOX4, CHAC1, and HIF1A were the prognostic biomarkers of gastric adenocarcinoma (Xiao et al, 2022). In addition, it was also found that the ferroptosis pattern in GC is related to the characteristics of immune microenvironment Liu S. J. et al, 2021;Wang F. et al, 2021). The establishment of markers associated with ferroptosis will help to predict the biological characteristics of GC and select the appropriate treatment for GC patients.…”
Section: Ferroptosis and Gastric Cancermentioning
confidence: 99%